Networks, Institutions, Culture and Association? A case study on associative actions in the German markets for organic food - Simon Dombrowski (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2017)
How does associative action shape market orders? While Economic Sociology has accumulated ample evidence on how networks, institutions and culture shape market valuations as well as competition and cooperation between market actors, little is known about the effect of organizing and associative actions on market order. Yet, - as is demonstrated by a historical case study of the German markets for organic food - associative action has an effect on market order by contributing to the constitution of market networks, institutions and cultures. Moreover, associative actions develop dynamics that are neither reducible to any of those social structures. The German markets for organic food are an extreme case of nine cooperating and competing organic farmers associations deliberately attempting to create a market order by developing and promoting organic production techniques, organic marketing channels and cultural frames about what the market is about and how producers are successful in a market. By applying a Neil Feldstein's field theoretic approach to markets to the German markets for organic food products this paper extends the scope of his approach from "producer markets" to markets where a large number of small, relatively resourceless producers compete.
Keywords: 330; German markets for organic food products; organic farmers associations; Bioland; Demeter; Naturland; markets as fields; business associations; organization of markets; product label